Love, sex and marriage in the Middle Ages : a sourcebook - McCarthy, Conor (London Routledge, 2022)
"This updated edition collects an extensive range of evidence for how people in the European Middle Ages thought about the emotional state of love, the physical act of sex and the social institution of marriage. With an expanded range of texts, wider geographical scope, suggestions for further reading and updated explanatory material to reflect changes in scholarship in over two decades, this edition is an invaluable resource for students interested in sexuality, gender, and relationships in the Middle Ages"--
Includes bibliographical references and index.
Keywords: Marriage -- Sources; Marriage -- England -- Sources; Sex -- Sources; Sex -- England -- Sources; Families -- Sources; Families -- England -- Sources